2019
DOI: 10.3390/ijerph16081341
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the Factors Associated with ADL-Related Disability among Older People in Six Middle-Income Countries: A Cross-Country Comparison

Abstract: The low- and middle-income countries (LMICs) are experiencing rapid population ageing, yet knowledge about disability among older populations in these countries is scarce. This study aims to identify the prevalence and factors associated with disability among people aged 50 years and over in six LMICs. Cross-sectional data from the World Health Organization (WHO) Study on global AGEing and adult health Wave 1 (2007–2010) in China, Ghana, India, Mexico, the Russian Federation, and South Africa was used. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
65
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 45 publications
10
65
1
1
Order By: Relevance
“…In a study in Netherlands, age was reported as one of the most important predictors of disability (6). In another study conducted in 6 middle and low-income countries, older age, were also identi ed as the important factor affecting disability (7). Our study results were in agreement with these results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a study in Netherlands, age was reported as one of the most important predictors of disability (6). In another study conducted in 6 middle and low-income countries, older age, were also identi ed as the important factor affecting disability (7). Our study results were in agreement with these results.…”
Section: Discussionsupporting
confidence: 92%
“…In another study conducted in 6 middle and low-income countries (India, Ghana, South Africa, Mexico, Russia, and China), age, chronic diseases (such as hypertension, angina, stroke, diabetes, chronic lung disease, asthma, and arthritis) and depression were identi ed as the most important factors affecting disability. Other factors (such as gender, marital status, education, social capital, physical activity, BMI) either had no role or played a different role in societies (7).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review from 2015 concluded that multimorbidity predicts future functional decline in adults, but comparisons between studies are hampered by the heterogeneity in definitions and operationalizations of multimorbidity and functional decline and the included cohort studies had short follow-up time (1-3 years) [9]. Later studies including four cross-sectional and two cohort studies with 1 and 2 years follow-up time have also found associations between multimorbidity and ADL/IADL disability [34][35][36][37][38]. It may seem that disease combinations including depression and cognitive impairment increase the risk for ADL/IADL disability substantially compared to combinations of only somatic disease [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may be of salient relevance for devising more targeted and effective interventions to prevent the onset of functional limitations among community-dwelling older adults. ) found that the prevalence of functional disability among older people ranged from 16.2% in China to 55.7% in India [8].Greater attention has been paid to exploring the correlates concerning the health and well-being of older adults [9]. Previous studies from China and abroad have both found that advanced age [10,11], frailty [12,13], depression [14] underweight or obesity, physical inactivity, a poor self-rated health, less engagement in level social activities, and pain [15] were most commonly associated with the incidence of ADL or IADL disability.…”
mentioning
confidence: 99%
“…Our findings may be of salient relevance for devising more targeted and effective interventions to prevent the onset of functional limitations among community-dwelling older adults. ) found that the prevalence of functional disability among older people ranged from 16.2% in China to 55.7% in India [8].…”
mentioning
confidence: 99%